2022
DOI: 10.2196/32396
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacy-Based eHealth Intervention Promoting Correct Use of Medication in Patients With Asthma and COPD: Nonrandomized Pre-Post Study

Abstract: Background Asthma and chronic obstructive pulmonary disease (COPD) affect millions of people worldwide. While medication can control and improve disease symptoms, incorrect use of medication is a common problem. The eHealth intervention SARA (Service Apothecary Respiratory Advice) aims to improve participants’ correct use of inhalation medication by providing information and as-needed tailored follow-up support by a pharmacist. Objective The primary aim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…Indeed, there is evidence to support that pharmacist care is associated with improvements in medication compliance among patients with COPD. 32,33 Russell and colleagues 34 have suggested that community-based practitioners' existing relationships with patients make them well positioned to support COPD patients with self-management. In the same vein, O'Connell et al 17 found that patients want "prompt, physically accessible support, " which could be delivered in part by community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence to support that pharmacist care is associated with improvements in medication compliance among patients with COPD. 32,33 Russell and colleagues 34 have suggested that community-based practitioners' existing relationships with patients make them well positioned to support COPD patients with self-management. In the same vein, O'Connell et al 17 found that patients want "prompt, physically accessible support, " which could be delivered in part by community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Service Apothecary Respiratory Advice is a multicomponent intervention stimulating correct use of inhaler therapy in asthma and COPD. 38 Although this intervention has shown potential to decrease exacerbation rates and improve adherence, this application appears to lack a theoretical underpinning. We therefore developed the RACE instrument to support selfmanagement in asthma and COPD with an integrated theoretical basis adopting TDF and BCTs to further enhance existing interventions in their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these instruments do not highlight specific underlying barriers concerning inhalation therapy requiring behaviour change. Furthermore, the Service Apothecary Respiratory Advice is a multicomponent intervention stimulating correct use of inhaler therapy in asthma and COPD 38 . Although this intervention has shown potential to decrease exacerbation rates and improve adherence, this application appears to lack a theoretical underpinning.…”
Section: Discussionmentioning
confidence: 99%
“…This was statistically significant for LAMA, LABA and LABA-ICS combinations but not for the LABA-LAMA association. Schnoor et al found that, with regard to COPD, men were more likely to be adherent than women [ 49 ]. An explanation could be that women were more likely to have more severe symptomatology than men for the same level of airway obstruction, for example having greater dyspnea and a lower body mass index.…”
Section: Discussionmentioning
confidence: 99%